History of investment legislation system development of the Republic of China - Shan, Li (Bulletin of the Karaganda University “Law Series”, 2018)
The article analyzes the history of legislation development regulating legal relations in the field of foreign investment in the Republic of China. The development of laws on foreign investment on the basis of the form of the enterprise does not meet the requirements of economic development in the area of foreign investment in the republic of China. Therefore, development of a unified Law on foreign investment will continue to increase the transparency of policies and legislation, are widely distributed, except for situations with more stringent national regime. By the only way China will be able to create more open, transparent investment environment with equal competition, stimulating the development of China’s economy. The article treats that these laws determine the legal grounds (bases) for the implementation of activities of foreign investors, the procedure of providing guarantees to foreign investors in China. It is affirmed that China strives for carrying out a flexible and transparent policy in the sphere of attracting foreign investments, granting privileges and preferences to foreign investors, but maintaining state control over the activities of foreign investors. A particular attention is drawn to the necessary of legal enforce and legitimate interests of investors in China need to raise to new heights, should create for foreign investments more stable, transparent and predictable legal environment.